The volume of liver irradiated during modern free-breathing breast radiotherapy: Implications for theory and practice. Issue 2 (May 2019) - Courtier, N.; Gambling, T.; Barrett-Lee, P.; Oliver, T.; Mason, M.D.
Abstract: Introduction: Incidental liver irradiation during breast radiotherapy can increase the risk of second primary malignancy and induce adverse inflammatory states. This study establishes the volume of liver irradiated during free-breathing breast radiotherapy. Novel associations between liver dose-volume data and systemic interleukin-6 soluble receptor and blood counts are evaluated. Methods: The volume of liver within the 10%, 50% and 90% isodose was determined for 100 women with stage 0 to II breast carcinoma undergoing 40Gy in 15 fractions over three weeks tangential irradiation. Blood counts and interleukin 6 soluble receptor concentration were recorded before, during and four weeks after radiotherapy. Dose-volume data for right-sided treatments was associated with longitudinal measures at bivariate and multivariable levels. Results: A maximum of 226cm 3 (19%), 92 cm 3 (8%) and 62 cm 3 (5%) of the liver was irradiated within the 10%, 50% and 90% isodose. Liver irradiation was almost exclusively a feature of the 52 right-sided treatments and was strongly correlated with breast volume ( ρ  = 0.7, p < 0.0001). Liver V10% was significantly associated with interleukin-6 soluble receptor concentration four weeks post-radiotherapy (beta = 0.38, p = 0.01) after controlling for theoretical confounding variables. Conclusion: Up to 8% of the liver is irradiated within the primary beam during local right-sided breast radiotherapy. Select use of a deep inspiration breath hold technique would reduce this volume, and minimise the risk of radiation-induced malignancy and acute systemic elevation of inflammatory interleukin 6 soluble receptor. Highlights: A portion of the liver is irradiated for some patients during free breathing breast radiotherapy. The likelihood of liver irradiation increases with breast size/volume. Low dose to a larger volume of liver associated with a systemic inflammatory mediator.